Decentralization Policy And Tourism Development: A Case Study Of Lombok Island, Indonesia - Furqan, Alhilal (2014)
Decentralization is a transfer of authority to perform some service to the public from an individual or an agency in central government to any other individual or agency which is closer to the public to be served at the local level. It has influenced major sectors in Indonesia including tourism at local levels. Decentralized tourism governance as an alternative form of administration has been suggested to overcome the potential problems that may result from the centralized governance. The potential benefits of the decentralized tourism governance, when it is implemented properly, could offer better efficiency in tourism sector. Through decentralization, plans can be fitted for local areas using comprehensive information that is only available at the local level, and inter-organizational coordination can be reached locally. Innovation and improvement can be promoted by decentralization, and this can enhance the possibility of producing more effective development strategies.